2019
DOI: 10.2147/ceg.s178179
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Syferol-IHP for the treatment of peptic ulcer disease: a pilot, double-blind randomized trial

Abstract: BackgroundTo our knowledge, there is no prior randomized study on the utility of Syferol-IHP (blend of virgin coconut oil and Ocimum sanctum oil) when coadministered with a triple therapy schedule.AimThis study determined the efficacy and safety of Syferol-IHP as adjunct to conventional triple therapy for the treatment of peptic ulcer disease (PUD).MethodsA pilot double-blind randomized trial was conducted in patients with confirmed diagnosis (endoscopy-guided biopsy) of PUD. Eligible patients were randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…Duodenal ulcer is a common and frequently occurring disease affecting 10%-15% of population in all geographical regions around the world. e occurrence and recurrence of DU seriously affects the quality of human life [23]. Currently, the prevention and treatment of DU mainly include clinical use of antacids, proton pump inhibitors, and H 2 receptor antagonists [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Duodenal ulcer is a common and frequently occurring disease affecting 10%-15% of population in all geographical regions around the world. e occurrence and recurrence of DU seriously affects the quality of human life [23]. Currently, the prevention and treatment of DU mainly include clinical use of antacids, proton pump inhibitors, and H 2 receptor antagonists [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…A former study conducted by Hassan et al, 2019 also showed no significant change between the two groups before and after treatment [20]. similar results was also showed by [21].…”
Section: Discussionsupporting
confidence: 67%
“…The latter effort was fostered by engaging with Nigeria’s Natural Medicine Development Agency within the Federal Ministry of Science and Technology, natural medicine developers and practitioners, and research clinicians to explore investigator-initiated studies on Nigerian natural products. 21 Beyond the rigorous assessment of natural medicines, other anticipated benefits of ACTC include the expansion of Africa’s cost-effective clinical capabilities that meet global standards, acceleration of clinical trial timelines in Africa, incorporation of a translational research mentality into Africa’s research institutions, and additional definition and institutionalization of the continent’s regulatory systems.…”
Section: Introductionmentioning
confidence: 99%